From the Tauriscan Gold Mine to the Goldenhorn and the Unusual Alpine Animal Od zlata pri Tavriskih do Zlatoroga in nenavadne alpske živali - Šašel Kos, Marjeta (Studia mythologica Slavica, 2015)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Three themes are analysed in the article, which are related under certain aspects to each other. These are the discovery of a rich gold deposit in the land of the Taurisci, mentioned by the Greek historian, Polybius, and the geographer and historian, Strabo; the folk-tale of the Goldenhorn/Zlatorog, in which the search for gold and treasure is reflected; and the third, the peculiar Alpine animal mentioned by the same Greek writers. It could be interpreted as a mythic animal, although in view of the accurate description, the animal was probably an elk.